EVALUASI PELAYANAN KINERJA PADA BADAN KESATUAN BANGSA DAN POLITIK KOTA TERNATE TAHUN 2017 - Marno Wance (Department of Public Administration, Muhammadiyah University of Makassar, 2019)
Abstract Public services and accountability of the government of Ternate City must be increased to serve the needs of the community and carry out the supervision function of the social and political conditions. The supervision function can be done through the aspect of performance evaluationconducted to measure the implementation of work programs at the National Unity and Political Agency in Ternate City in 2016. The evaluation was carried out as a basis for developing the program in the future with a description of financial administration framework, program priorities, work plans that refer to Government Work Plans (Rencana Kerja Pemerintah). The method of this study is qualitative using interview instruments and documentation. The approach used is directly from the respondent or the object under study, while the data sources are obtained through written documents namely the Strategic Plan of the City of Ternate in 2017 and the evaluation of the work programs. Analysis of government performance in this study uses the concept of service quality and service procedures to analyze research problems.Keywords: Public Service, Function of Supervision, Accountability of the Government of Ternate Abstrak Pelayanan publik dan akuntabilitas di Pemerintah Kota Ternat harus ditingkat untuk melayani kebutuhan masyarakat serta melakukan fungsi pengawasan terhadap kondisi sosial politk. Pada asepek evaluasi kinerja dilakukan untuk mengukur pelaksanaan program kerja pada Badan Kesatuan Bangsa dan Politik di Kota Ternate pada tahun 2016. Evaluasi dilakukan sebagai dasar untuk menyusun program pada tahun kedepan dengan kerangka penjabaran administrasi keuangan, prioritas program, rencana kerja yang mengacu pada Rencana Kerja Pemerintah (RKP). Metode yang digunakan dalam penelitian ini adalah kualitatif dengan menggunakan instrument wawancara serta dokumentasi. Pendekatan yang digunakan langsung dari responden atau objek yang diteliti, sedangkan sumber data adalah sumber data yang diperoleh melalui dokumen-dokumen tertulis yaitu Rencana strategis Pemerintah Kota Ternate Tahun 2017 dan Evaluasi program kerja. Analisis kinerja pemerintah pada penelitian ini menggunakan konsep kualitas pelayanan, prosedur pelayanan untuk menganalisis permasalahan penelitian.Kata kunci: Pelayanan Publik, Fungsi Pengawasan, Akuntabilitas Pemerintah Ternate